Rapid Synthesis of Fused Polycyclic Heteroaromatics through Successive Vinylic/Aromatic C−F Bond Activation. Issue 37 (8th August 2022) - Fujita, Takeshi; Fukuda, Takuya; Suzuki, Naoto; Ichikawa, Junji
Abstract: The synthesis of fused polycyclic heteroaromatics was achieved via successive vinylic / aromatic carbon−fluorine (C−F) bond activation. The Suzuki‐Miyaura coupling of (1‐bromo‐2, 2‐difluorovinyl)biaryls with 2‐hydroxy‐ or 2‐aminophenylboronic acids (esters) followed by defluorinative 5‐ endo ‐ trig cyclization yielded 2‐fluorobenzofurans (indoles) with a biaryl moiety in one‐pot operation. The obtained 2‐fluorobenzoheteroles underwent acid‐mediated intramolecular C−F/C−H coupling to yield tetra‐, penta‐, and hexacyclic heteroaromatics. This protocol allowed the synthesis of various substituted benzo‐fused dibenzofurans and carbazoles. Abstract : The synthesis of fused polycyclic heteroaromatics was achieved via successive vinylic / aromatic C−F bond activation. The Suzuki‐Miyaura coupling of bromodifluoroalkenes with 2‐hydroxy‐ or 2‐aminophenylboronic acids (esters) followed by defluorinative 5‐ endo ‐ trig cyclization afforded 2‐fluorobenzoheteroles bearing a biaryl moiety in one‐pot operation. Subsequent acid‐mediated intramolecular C−F/C−H coupling afforded tetra‐, penta‐, and hexacylic heteroaromatics.